Socio-Cultural Standards Promoted by the Mass Media as Predictors of Restrictive and Bulimic Behavior - Izydorczyk, Bernadetta; Sitnik-Warchulska, Katarzyna; Lizińczyk, Sebastian; Lipowska, Małgorzata (Frontiers in Psychiatry, 2020)
Research lacks in verifying the nature of the relationship between mass media pressure, body image, and the risk of unhealthy eating behaviors. This study aimed to investigate whether the internalization of sociocultural norms, perceived pressure or searching for information about body image promoted by the mass media directly affect restrictive and bulimic behavior towards eating, through the mediating role of body image and physical appearance variables. The research hypotheses were that (1, 2) body image, the pressure and the internalization of sociocultural norms are significant predictors of unhealthy eating behavior among women and men; and (3) the variables related to body image play the role of the mediating variable between the impact of socio-cultural standards of body image promoted by the mass media and unhealthy eating behavior. The sample comprised 514 Polish men and women, aged 16 to 63 old (men M=24.35; SD=13.53; women M=24.77; SD=7.61), with average Body Mass Index (BMI). Assessment comprised the Sociocultural Attitudes Towards Appearance Scale (SATAQ-3), Eating Disorders Inventory (EDI 3), The Multidimensional Body-Self Relations Questionnaire (MBSRQ-AS), and the author’s survey questionnaire. The descriptive and comparative statistics, and a path analysis (structural equations modeling) were applied. The statistical analysis showed that the variables related to body image do not play the role of intermediary variables. The pressure of sociocultural standards of body image and physical appearance had the strongest and most direct effect on the development of restrictive eating behavior and appeared to negatively affect body image in women. The search of information on body image in the mass media had the strongest and most direct impact on the development of bulimic eating behavior among women. However, only the global internalization of sociocultural standards of body image and physical appearance had a significant and direct effect on the development of bulimic eating behavior in men. Moreover, the internalization of athletic body shape standards had the strongest and most positive impact on some aspects of body image in this group. No sociocultural variables showed a direct impact on restrictive behavior among studied men. BMI had a positive and direct impact on individual body part satisfaction.